Ensino do corpo humano: mediações teatrais na formação inicial de professores para além das partes - LEÃO, Cássia Nunes (2020)
The body has been object of study of diverse fields of sciences, with the perspective of understanding it in its multidimensionality. However, in spite of this fact, in the teaching of sciences, the human body is presents divided into "parts", whose approach is based on the anatomical and physiological perspectives The approach of the human body requires, in addition to its incidence on the biological dimension, the consideration of contemporary events. Through the theater (the production of theatrical sketches), we seek to understand in what terms a formative experience, involving the theme human body, contribute to the critical and reflexive apprehension of one of the dimensions that constitute it - the social dimension, precisely in the approach to the subject obesity, as a social scene of the present times. Qualitative approach, in the form of research-training, constituted the methodological option. The subjects of the research were represented by three undergraduate students of the Licenciatura Integrada em Educação em Ciências, Matemática e Linguagens, of Instituto de Educação Matemática e Científica, of Universidade Federal do Pará. The narratives were submitted to the interpretative analysis. The formative experience show that the undergraduate students constructed a scenic discourse with criticality and creativity and a proper way of problematizing aspects associated with obesity. They highlighted the daily life of society, with regard to the celerity of the present life in the configuration of obesogenic feeding behaviors, away from the understanding of the human body unrelated to society, with all its entanglements circumscribed.